Field survey of air conditioner temperature settings in hot, humid climates, part 1: questionnaire results on use of air conditioners in houses during sleep - N. Ekasiwi, Sri Nastiti; Abdul Majid, Noor Hanita; Hokoi, Shuichi; Oka, Daisuke; Takagi, Nozomi; Uno, Tomoko (Architectural Institute of Japan, 2013)
This paper presents the results of a questionnaire survey on the use of air conditioners in houses in Surabaya, Indonesia, and Kuala Lumpur, Malaysia. The objective of the survey was to clarify what temperature and humidity levels people in these regions prefer in order to feel comfortable, with special focus on their sleeping environment. This was determined through survey responses and by measuring the thermal environments in their bedrooms. The questionnaire file was distributed to 64 university students in Surabaya and 65 in Kuala Lumpur. The students interviewed their family members and described their own experiences in their daily lives at home. The survey results show that the respondents set their air conditioners at very low temperatures. They also show that more than half of the respondents reported a cold or cool thermal sensation while using the air conditioner. Many respondents also reported various health problems and feeling cold while they were sleeping.